Assessment of Causes and Effects of Corporate Restructuring - Kinga BAUER (Communications of International Proceedings, 2020)
Constant changes that take place in the economic environment of enterprises force them to constantly adapt to current conditions. Ignoring changes can cause serious crises and even bankruptcy of companies. A method of counteracting crisis situations, as well as a method of overcoming them, is the restructuring process. In the event of a crisis situation, the starting point is restructuring aimed at remedial actions, and only then taking development measures. Carrying out restructuring requires a series of analyses to determine the grounds and effects of the changes which have been implemented. The goal of the article was to determine the measures used in the diagnosis of the needs and effects of restructuring, as well as the importance of plans and forecasts in the assessment of the implemented changes. In order to achieve this goal, literature studies and surveys in the form of questionnaires were conducted on a group of restructuring specialists. As a result of the conducted research, it was found that there is no uniform set of indicators used in the restructuring process to assess the need to restructure and the achieved results. Popular indicators for diagnosing the needs and effects of restructuring are liquidity, solvency and profitability ratios. Restructuring specialists also identified as important, information on the company's plans, forecasts, goals and strategy which could affect its future cash flow.
Keywords: corporate restructuring; financial measures; financial statement; financial ratios